PENGARUH TAX AVOIDANCE DAN FIRM SIZE BESERTA VARIABLE LAINNYA TERHADAP FIRM VALUE - Ryan, Nicholas; Suryanto, Suryanto (E-Jurnal Akuntansi TSM, 2024)
Abstract: This study aims to provide empirical evidence regarding the influence of tax avoidance, profitability, liquidity, leverage, firm size, and dividend policy on firm value. The population in this study consists of companies in the cyclicals and non-cyclicals sectors listed on the IDX from 2020 to 2022. The sample was obtained using purposive sampling method, with 35 companies selected as the sample, resulting in a total of 103 data points after outlier testing. This research uses multiple linear regression model to test hypotheses and to analyse the data. The results of this study indicate that profitability, liquidity, and leverage have an influence on firm value. However, tax avoidance, firm size, and dividend policy do not have an influence on firm value. Keywords: firm value, tax avoidance, profitability, liquidity, leverage, firm size, dividend policy